Tracing the links between crime, punishment, and inequality: a challenge for the social sciences - Lacey, Nicola (Tracing the relationship between inequality, crime, and punishment, 2020)
The propositions that social inequality shapes crime and punishment, and that crime and punishment themselves cause or exacerbate inequality, are conventional wisdom. Yet, paradoxically, they are also controversial. In this volume, historians, criminologists, lawyers, sociologists and political scientists come together to try to solve this paradox. This introduction examines some of the main intersections and points of productive dialogue emerging from the essays, organised around two key themes: the insights to be gained by moving between different levels of analysis; and the importance of the perspective provided by comparative and historical lenses. It concludes that a high crime/punishment/inequality equilibrium is associated with deep failures of incorporation, integration and inclusion in the social, political and economic systems which it afflicts. And these failures of inclusion operate in terms of certain key dynamics: segregation; de facto or de jure disenfranchisement; and failures of coordinating capacity which are premised not only on institutional design but also on the diversity of and conflict between interests.